A construção de uma imagem: as biografias dos presidentes Juscelino Kubitschek, João Baptista Figueiredo, Luiz Inácio Lula da Silva, Dilma Rousseff e Jair Messias Bolsonaro - Paula, Gabriel Jorge de Quadros de (2023)
Tese (Doutorado)